Subjectivity issue in “City of Glass” by Paul Auster Based on Žižek’s Perspective - Mohammadkarimi, Ebrahim; Yousefi Azar, Shirzad (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2024)
The concept of lack being the apex of today’s human being’s stratums of dithered truth is an equivocated issue in the contemporary postmodern era. As is for the amalgamation of postmodern approaches toward subjectivity, the subject is decentered, displaced, and/or pluralized; for Slavoj Žižek, on the contrary, the very lack is inherent in the very core of subjectivity. In Paul Auster’s City of Glass, a juxtaposition of both the postmodern approach and that of Žižek’s Neoclassical revisiting of subjectivity is presented. The protagonist, who is a detective in this novella, acts as if he lags behind some internal reality. For Paul Auster, the detective genre is not the conventional one; that of the classical detectives who search for clues as a means to reach causality to work out the case; it is rather a genre so confusing that the detective not only does not yield any definite result, but with his ebullient sentiments exculpate himself as a detective from coming to any logical deduction. Taking City of Glass as the center for the present discussion, this paper, in an analytic approach, is to render a rereading of the novella now from a Žižekian perspective.